Stationarity of I-mode operation and I-mode divertor heat fluxes on the ASDEX Upgrade tokamak. (January 2019) - Happel, T.; Griener, M.; Silvagni, D.; Freethy, S.J.; Hennequin, P.; Janky, F.; Manz, P.; Prisiazhniuk, D.; Ryter, F.; Bernert, M.; Brida, D.; Eich, T.; et al.
Highlights: Robust and stationary I-mode operation with neutral beam injection has been obtained on the ASDEX Upgrade tokamak by applying feedback control mechanisms to the heating power. The impact of the weakly coherent mode, often connected to I-mode operation, on both density and electron temperature fluctuations is analyzed. It is found that the density perturbation is a factor of 2 stronger than the electron temperature perturbation. Divertor heat fluxes are investigated. The upstream power fall-off length scales with the SOL temperature fall-off length. Furthermore, transient divertor heat fluxes are investigated, which are connected to turbulence bursts observed in the confinement region of the I-mode plasma [T. Happel et al., Plasma Phys. Control. Fusion 59, 014004 (2017)]. Abstract: Recent I-mode investigations from the ASDEX Upgrade tokamak are reported. It is shown that neutral-beam-injection heated I-modes can be stationary, which is important in terms of extrapolability towards future fusion devices. Furthermore, detailed studies on the weakly coherent mode are reported. In particular, experimental observations point towards its existence in L-mode, before I-mode starts. Moreover, its impact on density and temperature fluctuations is evaluated. Studies of stationary divertor heat fluxes show that in I-mode, the upstream power fall-off length is between those observed in L-mode and H-mode, and it is connected to the scrape-off layer temperature fall-off length. Moreover, analysis of transient divertor heat loads shows that intermittent turbulent events, observed in the confinement region and linked to the weakly coherent mode, are responsible for a significant part of divertor heat loads.